1993
DOI: 10.3109/07357909309024847
|View full text |Cite
|
Sign up to set email alerts
|

Combined Modality Therapy Increasing Local Control of Pancreatic Cancer

Abstract: Twenty patients with inoperable locally advanced Stage II and III pancreatic cancer were treated with combined modality therapy. Radiotherapy consisted of split courses of 2000 cGy each and, as needed, an additional 1400 cGy, separated by 2-week intervals. Simultaneous multidrug regimen chemotherapy consisted of 5-fluorouracil, continuous infusion, 1 g/m2 days 1-5; streptozotocin, 300-500 mg/m2 days 1, 2, 3; and cisplatin, 100 mg/m2 day 3 of every 4-week radiotherapy course (RT-FSP). Primary tumors decreased m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Systemic chemotherapy in advanced pancreatic carcinoma has not been significantly better than supportive therapy alone. Median survival for com bination regimens range from 3 to only 6.5 months and are probably not longer than those obtained with 5-FU alone [4], Radiotherapy in combination with systemic chemotherapy (5-FU and others) was associated with a median survival of 10-12 months in localized advanced nonresectable cases [5][6][7], Even after resection, the me dian survival times rarely exceed 12 months. Again, only postoperative intensive radiochemotherapy has produced significant evidence of prolonged survival, as demon strated in a single randomized study [8], Since the results of that study still need confirmation by other groups, up to now, no postoperative treatment can be regarded as firm ly established.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic chemotherapy in advanced pancreatic carcinoma has not been significantly better than supportive therapy alone. Median survival for com bination regimens range from 3 to only 6.5 months and are probably not longer than those obtained with 5-FU alone [4], Radiotherapy in combination with systemic chemotherapy (5-FU and others) was associated with a median survival of 10-12 months in localized advanced nonresectable cases [5][6][7], Even after resection, the me dian survival times rarely exceed 12 months. Again, only postoperative intensive radiochemotherapy has produced significant evidence of prolonged survival, as demon strated in a single randomized study [8], Since the results of that study still need confirmation by other groups, up to now, no postoperative treatment can be regarded as firm ly established.…”
Section: Introductionmentioning
confidence: 99%
“…The authors had applied 54 Gy radiotherapy together with 5-FU continuous infusion, streptozotocin and cisplatinum (RT-FSP), followed by systemic CT with 5-FU and folinic acid. The local tumour control was excellent with an overall primary tumour response rate of 63% [11]. Thirty percent (30%) of the whole patient group were resectable after downstaging, and the resectability was 67% in the 30 patients surgically explored for a resection.…”
Section: Neoadjuvant Treatmentmentioning
confidence: 82%
“…Foo et al [5] reported that 54 Gy ± chemotherapy was more effective at reducing local recurrences than irradiation with 45 Gy but this was an uncontrolled study [5]. The occurrence of liver metas tasis is not influenced by radiotherapy ( ± chemotherapy) in the adjuvant, neoadjuvant or palliative settings [4,5,[19][20][21][22][23] nor by systemic adjuvant chemotherapy [ 18].…”
Section: Discussionmentioning
confidence: 99%